Financial Management Behavior Of College Students: Potential Factors And Tri-Nga - Erawati, Teguh; Gadi Rara, Wiwin Leona (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to confirm the influence of financial literacy and Tri-Nga teaching, which includes Ngerti (Understanding), Ngroso (Feeling), and Ngelakoni (Doing), on student financial management behavior. The study population and sample consisted of 106 students majoring in Accounting at Sarjanawiyata Tamansiswa University. Data collection was conducted through the use of questionnaires, while data analysis used validity and reliability test techniques to assess data quality. Furthermore, classical assumption tests such as normality, heteroscedasticity, and multicollinearity were used to ensure data conformity with the assumptions required in regression analysis. Hypothesis results were obtained from the analysis using the T, F, and R2 tests using SPSS version 23 software. From these results, it is concluded that financial literacy has a positive and significant impact on student financial management behavior. Meanwhile, the Tri-Nga Teachings also showed a positive and significant impact on students' financial management behavior. Simultaneously, financial literacy and Tri-Nga Teachings also have a positive and significant influence on students' financial management behavior.